Development of Sustained Release Preparations of Metoclopramide Hydrochloride Based on Fatty Matrix - Nargis, Monnujan; Islam, Md Saiful; Naushin, Fatima; Haider, Syed Shabbir (Dhaka University Journal of Pharmaceutical Sciences, 2013)
Sustained release formulations of metoclopramide HCl (4-amino-5-chloro-N-(2-diethylaminoethyl)-2- methoxybenzamide hydrochloride) (MH) were prepared using carnauba wax (CW) and stearic acid (SA) as matrix formers. Granules were prepared by melt granulation method while direct compression technique was used to prepare the tablets. The drug release profiles of these products were studied by in-vitro dissolution testing in simulated gastric, gastrointestinal and intestinal media of pH 1.2, 4.5 and 7.5, respectively. The increase in the proportion of SA in the granules produced a concomitant decrease of the initial drug release rate but later on the release rate was enhanced in the intestinal medium. Drug release was found to be affected by compression force and stirring rate but also showed a dependency on pH of the dissolution fluid. The fastest release rate was found at pH 4.5 and the slowest at pH 1.2 which was consistent with the drugs solubility behavior. Matrix erosion and water uptake rates were highest in the intestinal medium and lowest in the gastric medium. The drug release kinetics followed the Higuchis model in all cases. DOI: http://dx.doi.org/10.3329/dujps.v11i2.14563 Dhaka Univ. J. Pharm. Sci. 11(2): 129-136, 2012 (December)